2019
DOI: 10.1136/bmjqs-2019-009545
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy medication review, death and re-admission after hospital discharge: a propensity score-matched cohort study

Abstract: BackgroundIn-hospital medication review has been linked to improved outcomes after discharge, yet there is little evidence to support the use of community pharmacy-based interventions as part of transitional care.ObjectiveTo determine whether receipt of a postdischarge community pharmacy-based medication reconciliation and adherence review is associated with a reduced risk of death or re-admission.DesignPropensity score-matched cohort study.SettingOntario, CanadaParticipantsPatients over age 66 years discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“… 45 Utilization of these services to target those most likely to benefit overall, such as older adults or people taking numerous medications, has been mixed, yet recent Canadian research has demonstrated that medication reviews are associated with a small reduced risk of readmissions to hospital and death. 44 , 46 , 47 …”
Section: Primary Care Services Offered By Community Pharmaciesmentioning
confidence: 99%
“… 45 Utilization of these services to target those most likely to benefit overall, such as older adults or people taking numerous medications, has been mixed, yet recent Canadian research has demonstrated that medication reviews are associated with a small reduced risk of readmissions to hospital and death. 44 , 46 , 47 …”
Section: Primary Care Services Offered By Community Pharmaciesmentioning
confidence: 99%
“…12 13 However, some researchers have pointed out that aged patients with chronic diseases who received transitional care are still adversely affected as a result of low intensity of information support in transitional care. [14][15][16] These patients, who are repeatedly transferred from hospitals to their homes often do not get high-quality information support; resulting Open access in a poor quality of continuing care, especially in medication information and discharge plan implementation. [17][18][19][20] Therefore, for this special vulnerable group, we need to ensure high-intensity information support in carrying out their transitional care.…”
Section: Introductionmentioning
confidence: 99%
“…Although most jurisdictions supporting medication reconciliation or MR for people moving from hospitals into the community provide procedural guidance on how to conduct a reconciliation or review, the reality of practice introduces variations. 15 16 Results from individual studies vary significantly, some indicating that MR after hospital discharge may have benefit in reducing hospital readmissions or emergency hospital visits, [17][18][19][20] others casting doubt that tangible outcome benefits can be achieved 21 or producing evidence of a negative effect. 22 23 The majority of studies and subsequent systematic reviews focus on outcomes as a result of an MR, they provide limited detail as to how these outcomes have been achieved or explore the differing contexts that may have led to contradictory results.…”
Section: Introductionmentioning
confidence: 99%